Digital Literacy as an Instrument for Youth Empowerment and Creativity in Nonformal Education - Bondan Dewabrata; Supriadi; Rosnindar Rahardjo; Akis Jasuli; Annisa Syakina; Yowanda (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the level and role of digital literacy among creative youth at the Muhammadiyah Orphanage in Sumenep within a non-formal educational context. A qualitative research design was employed, with data collected through in-depth interviews, participatory observation, and digital documentation analysis. The data were analyzed using thematic analysis to identify patterns related to digital literacy competencies and their contribution to creative practices. The findings reveal that the digital literacy level of orphanage youth is predominantly basic, with skills concentrated on technical and operational use of digital devices and social media platforms. Higher-order competencies, including critical evaluation of information, verification of digital content, and awareness of digital security, remain limited. However, ethical awareness in basic digital interactions is relatively well established. Despite these limitations, digital literacy has begun to facilitate creative expression, particularly through simple visual and audiovisual content production, which positively influences self-confidence and social engagement among the youth. These findings demonstrate that even at an elementary level, digital literacy can function as a catalyst for creativity and empowerment when aligned with youth interests. The study underscores the need for structured and context-sensitive digital literacy programs in non-formal educational institutions to strengthen critical awareness, creative capacity, and sustainable empowerment for marginalized youth in the digital era.